IDENTIFIKASI DAN ANALISIS STRUKTUR RANTAI PASOK KOPI RAKYAT ROBUSTA KECAMATAN BANGSALSARI, JEMBER - Novita Fitri Yulian; Nita Kuswardhani; Winda Amilia (JURNAL AGROTEKNOLOGI, 2019)
Robusta coffee is one of the crops plantation that cultivated in the most area in Indonesia. Bangsalsari District, Jember Regency is one of location area on the Argopuro Mountain slope, with total Robusta coffee production about 9,945.80 quintals in 2016. The robusta coffee supply chain is a supply concept which has system settings related to product flow, information flow, financial flow, service flow and actor complicity in each flow. The purpose of this study was to determined the structure of the robusta coffee supply chain in Bangsalsari District, Jember Regency. The data collecting method used in this research were primary and secondary data. The primary data was taken from the results of interviews, observation and documentation, while secondary data obtained from the literature studies, internet, journals and other documents as relevant references. The results showed that the structure of the robusta coffee supply chain in Bangsalsari District, consisted of several supply chain groups or called actors. Supply chain groups were farmers, collectors, wholesalers, exporters and related institutions. Keywords: actor, robusta coffee, supply chain